Self-regulation in the use of social media: an obvious but tricky choice? - Zulhuda, Sonny (2016)
In Malaysia, social media had increasingly become a choice for public communications both at social and commercial spheres. The emergence of the digital natives together with a better connectivity had flourished the use of online accounts such as Facebook, Twitter, Instagram and Linkedin – among others. The primary legislation regulating telecommunications and Internet industries, i.e. the Communications and Multimedia Act (CMA) 1998 had provided a beautifully designated self-regulatory mechanism for the Internet industries in governing their content. Nevertheless, 18 years later, the notion of self-regulation is still far from public sight, let alone real practice. Most of the legal issues surrounding social media such as defamation, sedition, hate-speech as well as privacy breaches have been subject to various legislation; and disputes would in most cases find their way in the court rooms. This presentation is conducting a recent survey of how social media is regulated in Malaysia, more specifically picking up the cases of sedition, offensive speech and privacy breaches. It also highlights lessons learnt and proposed recommendations to move forward.